2013
DOI: 10.12720/jolst.1.1.1-6
|View full text |Cite
|
Sign up to set email alerts
|

The Probable Protective Role of Vitamin C against Cyclosporine an Induced Pulmonary Changes in Mice

Abstract: Cyclosporine A (Cs-A) is a frequently used immunosuppressive agent in transplant medicine to prevent rejection and in the treatment of autoimmune diseases. Vitamin c is a potent antioxidant that has the ability to scavenge factors causing free radical formation in animals receiving Cs-A. It play a major role in disease prevention. Cs-A induced histological and ultrastructural alterations in the pulmonary tissue. These included congestion and hemorrhage of most blood capillaries, increased number of lymphocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…Our results revealed that the third group which received 40 mg/kg/day of cyclosporine induced marked pulmonary histopathological abnormalities such as a pyknotic nucleus of pneumocyte type II, degeneration of alveoli with its microvilli, and emphysema with inflammatory cellular infiltration and pulmonary vessels congestion in consistency with Yousef and ALRajhi [ 16 ] while the second group which received 25 mg/kg/day of cyclosporine showed mild pulmonary ultrastructures and histopathological changes such as a shrinkage nucleus of pneumocyte type II, degenerated microvilli on the alveolar surface, thickened wall of bronchiole with moderately congested blood capillaries and macrophages infiltration in the alveolar spaces, and nearly normal architecture of alveoli with thickened interalveolar septa. Furthermore, the overall lung lesion severity scores were differed significantly between the second and third groups indicating that the severity of cyclosporine induced pulmonary histological changes depending on its dose.…”
Section: Discussionsupporting
confidence: 59%
“…Our results revealed that the third group which received 40 mg/kg/day of cyclosporine induced marked pulmonary histopathological abnormalities such as a pyknotic nucleus of pneumocyte type II, degeneration of alveoli with its microvilli, and emphysema with inflammatory cellular infiltration and pulmonary vessels congestion in consistency with Yousef and ALRajhi [ 16 ] while the second group which received 25 mg/kg/day of cyclosporine showed mild pulmonary ultrastructures and histopathological changes such as a shrinkage nucleus of pneumocyte type II, degenerated microvilli on the alveolar surface, thickened wall of bronchiole with moderately congested blood capillaries and macrophages infiltration in the alveolar spaces, and nearly normal architecture of alveoli with thickened interalveolar septa. Furthermore, the overall lung lesion severity scores were differed significantly between the second and third groups indicating that the severity of cyclosporine induced pulmonary histological changes depending on its dose.…”
Section: Discussionsupporting
confidence: 59%
“…The effects of CsA therapy on nephrotoxicity, kidney lesions, and creatinine levels have been previously reported [ 9 ]. CsA causes an increase in reactive oxygen species (ROS) and lipid peroxidation products, both of which have been linked to its toxicity [ 10 ]. CsA causes kidney damage, accompanied by an increase in inflammatory and oxidative stress markers [ 11 ].…”
Section: Introductionmentioning
confidence: 99%